A seventeen-year Research Topic Dispersion and Methodological Choices among LIS Postgraduates in Tanzania - Ndenje-Sichalwe, Esther; Elia, Emmanuel Frank (University of Dar es Salaam Library Journal, 2022)
The study explored research topics dispersal and research strategies of Library and Information Science (LIS) postgraduate students in Tanzania from 2000-2017. Data were collected from the East Africana research repository section of the UDSM Library and the Information Studies Programme (ISP) offices from June to November 2017. A total of 269 LIS dissertations were assessed using content analysis to classify research topics. Findings revealed topics extensively researched were information dissemination, information access and information seeking behaviour. Least researched topics were information privacy and ethics, reading habits and encouragement, copyright and Information policy. History of information science and librarianship, quantitative and qualitative research, multimedia, webometrics, human €“computer interaction, systems analysis, digital security, internet crime and information licensing and fair use were not researched. In addition, mixed research approach was mostly preferred by students but experimental and action research were least used. The study contributes in LIS education mapping in Tanzania and likely the first study to show topics selection based on globally accepted LIS classification schemes. The study gives an insight on research topics and research strategies used in higher learning organizations (HLIs) in Tanzania and arguably most developing countries. Findings may improve quality of research offered in LIS schools by supporting LIS postgraduate training and establishing library technology hubs and laboratories to match the world LIS research trend and order.